Economies, public finances, and the impact of institutional changes in interregional perspective the Low Countries and neighbouring German territories (14th-17th centuries) - Schaïk, Remi van 1950-; International conference "Economies, public finances, and the impact of institutional change" (Studies in European urban history, 2015)
"The way and extent to which differences in economic systems and stages of development, and the impact of institutional changes affected the political economy and fiscal systems of regions, or vice versa, is the overall theme of this volume. One major problem is the non-convergence of economic regions, financial networks, political borders and fiscal systems. The question is whether a set of variables is supra-regional, interregional, regional, local or even a mix of all of these. These questions have broad implications for our understanding of urban society and the relations between town and countryside. This volume contains studies about economic, financial and political structures, and developments in different regions of the Low Countries and the Lower Rhine area in a regional comparative perspective during the Late Middle Ages and the Early Modern Period."--Back cover